OPTIMIZATION OF MUNICIPAL WASTE COLLECTION POINTS IN YOGYAKARTA CITY- INDONESIA - Bertha Maya Sopha; Alditya Perkasa Sri Haryoto (Universitas Gadjah Mada, 2016)
Uneven capacity utilization seems to be a constant problem in Yogyakarta waste management system. The problem is worsen by lack of a decision tool to evaluate the system and formulate appropriate strategy.This present study therefore aims atevaluatingthe performance of existing waste management systemandoptimizingmunicipal waste collection points. A mathematical model of MixedIntegerLinearProgramming was developed and implemented inLingo 9. Findings show that the current waste management system is associated to daily total cost of about IDR 10 million and capacity utilization of 88%. Scenarios are developed to examine the optimized system. Findings suggest that current municipal waste can be handled with 35 collection points involving 15 depots and 20 containers. The optimized system is corresponding to IDR 6.3 millionand the capacity utilization of 99%, which makes a reduced cost of 37% and an increasedcapacity utilization of 13% in comparison to the performance of the existing system. Based on sensitivity analysis,volume of municipal waste appears to be influential factor toward the total cost and network structure. Limitation of the model is also discussed.